The Relationship between Philosophy, Balaghah, and the Qur'an: A Study of Manahij Tajdid fi an-Nahwi wa al-Balaghah wa at-Tafsir wa al-Adab by Amin Al-Khuli - Abdurrahman, Ja'far Rais; Zenrif, M. Fauzan (Program Studi Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Raden Fatah Palembang, 2023)
This paper discusses Amin Al-Khuli's views on the Science of Balaghah and its relationship with the sciences of Philosophy and Psychology, as well as highlighting manipulation in the Qur'an. This research focuses on the relationship between Balaghah and Psychology, using the library research method. The author uses the book